Votán-Zapata contra a Besta-fera: escritos do EZLN contra o capitalismo no México - Anjos, Diego Marques Pereira dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present master thesis has the object to study, the declarations of the Zapatista Army of National Liberation (EZLN), a Mexican political movement. Do we seek to understand the meaning of textual production of the EZLN through a selected set of texts in which the organization presents his world vision, his way of organization, the critique of capitalist society, their objectives.Our methodology had as its starting point the idea that to understand and explain a speech is necessary to discover the social conditions of production of discourse, and the work that follows is a presentation of the external motivations and of internal unity of the EZLN discourse. In the third part of our work, do we seek realize a critical reflection on the announcements by EZLN based on the concepts of ideology and utopia, and as a result of our reflection, we indicate that the EZLN presents a critical discourse on Mexican society, but don't develop a alternative and radical project of social transformation.

A presente dissertação de Mestrado tem como objeto de estudo os comunicados do Exército Zapatista de Libertação Nacional (EZLN), um movimento político mexicano. Buscamos compreender o significado da produção textual do EZLN através de um conjunto selecionado de textos em que a organização apresenta sua visão de mundo, sua forma de organização, a crítica da sociedade capitalista, seus objetivos. Nossa metodologia teve como ponto de partida a ideia de que para se compreender e explicar um discurso é necessário descobrir as condições sociais de produção do discurso e o trabalho que se segue é uma exposição das motivações externas e da unidade interna do discurso do EZLN. Na terceira parte de nosso trabalho buscamos realizar uma reflexão crítica sobre os comunicados do EZLN tendo como base os conceitos de ideologia e de utopia, e como resultado de nossa reflexão indicamos que o EZLN apresenta um discurso crítico sobre a sociedade mexicana, mas não desenvolve um projeto alternativo e radical de transformação social.
Keywords: Análise do discurso; Socialismo utopico; Ideologia; Mexico - Politica e governo; Ideology